Design of Corporate Performance Management Based on Integrated Performance Management System (Case Study: PT. IEV Pabuaran KSO) - Cornell, Axel William; Wibisono, Dermawan (Journal of Business and Management, 2016)
Abstract.As a growing oil company in KSO (Kerja Sama Operasi) industries, which is a partnership to state oil company Pertamina Upstream (EP), PT. IEV Pabuaran KSO (IEVPABKSO) performance is in need of improvements. As we know, oil price is dropping below US$ 35 USD/barrel which is close to the lifting cost of crude oil production, which forces every oil company in the market to adjust their strategy and adapt to the situation. IEVPABKSO also suffers a quite big loss in 2015 because of their failed drilling project, which led to zero production and negative profit margin for them, despite their target which to reach positive profit. IEVPABKSO have not yet implemented performance management system in their company, which leads to to inconsistent internal performance of their company. For 2016, the Integrated Performance Management System (IPMS) Framework are being used because of their flexibility to match any companies, whether profit or non-profit. The objective of the of this research is to determine the proper indicators or the KPIs, develop a performance management framework and analyze IEVPABKSOâ€™s performance through radar diagram. The data is gathered by focused questionnaire, having discussion with the general manager of IEVPABKSO and analyzing the internal data of the company. The vision and mission of IEVPABKSO will be analyzed by Vision Generator from Wibisono (2012) and the preferable KPIs is all taken from Panduan Penyusunan Indikator also from Wibisono (2011). After analyzing the available data and having discussion the the general manager, weâ€™ve come to an agreement that vision and mission of IEVPABKSO is already a good vision and mission. The KPIs that resulted from the questionnaire and the discussions with the management consists of 53 preferable KPIs with no Gap and False indicators. From the performance framework and the analysis, we can conclude that IEVPABKSO has a good performance in planning and estimating their costs. They should maintain their conditions and their current performance. Improvements need to be considered as their long-term plan.Keywords: Performance Management System, Key Performance Indicators, Performance Management Framework, Integrated Performance Management System, Oil Company, IEVPABKSO.Â